How sensory marketing elements attract customer to return to theme restaurant / Nuratirah Kamaludin ... [et al.] - Kamaludin, Nuratirah; Thamby Chik, Chemah; Bachok, Sabaianah; Sulaiman, Suria (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Cawangan Selangor, 2020)
Foodservice consumers in Malaysia continued to record powerful performance in 2018 as Malaysians continued to boost their appetite in eating away from home. Foodservice industry copes with the opportunity to manage customers and making sure all their needs and preferences are fulfilled. Sensory marketing has been recognized as one of the factors that could attract customers. The elements of sensory marketing such as visual, olfactory, auditory, tactile and gustative might be useful for every food service industry especially for customers in a theme restaurant to become fully immersed with sensory experiences. However, could sensory experiences attract them to return? This conceptual paper seeks to understand the sensory elements of sensory marketing that could have been adopted or adapted in theme restaurant to engage customers to return. This area of study is rarely discussed in Malaysia although it could be proven beneficial to boost restaurant industry generally. Keywords